The Concept of Love for Knowledge and Excellent Muslims in Transforming Human Capital: An Analysis on Gender Differences - Nur Hidayah Mohd Abd Malik; Syaidatun Nazirah Abu Zahrin; Fariza Md Sham; Rezki Perdani Sawai (UKM Press, 2024)
Non-Indexed Publication